Hospital acquisitions: The chief nurse executive perspective. Issue 6 (June 2018) - Robinson, Ruthie; Knight, Stacey
Abstract : Read about the experiences of hospital CNEs from rural facilities to major academic medical centers across the country who underwent an acquisition in this qualitative study.